Pinoy Cosplay Convention - Pineda, Melanie L. (Manila : National University, 2015)
Pinoy Cosplay convention is a place where fans of a particular film, television series, comic book, actor, or an entire genre of entertainment such as science fiction or anime and manga, gather to participate and hold programs and other events, and to meet experts, famous personalities, and each other. Some also incorporate commercial activity. Philippines have no permanent and official cosplay convention center. The SM Megatrade Hall, SB/IX convention Center and some open spaces inside the mall serves as Cosplay convention center of the cosplayers. Many events happen in different malls, it have a difficulty in terms of travel.
Chapter 1. The problem and its setting -- Chapter 2. Research methodology -- Chapter 3. Terms of references -- Chapter 4. Data gathering, collation and analysis of data -- Chapter 5. Design framework -- Chapter 6. Translations -- Chapter 7. Final revisions -- Annexes.
Keywords: CONVENTION CENTER